On vicarious ostracism. Examining the mediators of observers' reactions towards the target and the sources of ostracism. (2nd October 2017) - Paolini, Daniele; Pagliaro, Stefano; Alparone, Francesca Romana; Marotta, Federica; van Beest, Ilja
Abstract: Ostracism is a painful experience, to the point that even observing ostracism hurts. We extend research on vicarious ostracism by investigating how observers subsequently behave and whether this is driven by intrapersonal feelings (need satisfaction) and/or interpersonal impressions. Sixty-six participants observed either ostracism or inclusion in Cyberball. They reported their global impression of sources and of targets, their own need satisfaction, and how they wanted to allocate money towards sources and targets. Observing ostracism increased money donations to targets (and decreased donation to sources), which was mediated by both lowered need satisfaction and negative impressions towards the sources, with stronger effect emerging for the latter mediator. These findings advance knowledge about the mechanisms underlying interpersonal behavior after vicarious ostracism.